Peran Tim Rumah Pelita di Kota Semarang - Amelia Putri Anggraeni; Ilyas Ilyas (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the role of the Rumah Pelita team in addressing stunting among children under two years old and in conducting maternal classes in Semarang City. The research uses a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings on the team's role in handling stunting and conducting maternal classes cover three stages: planning, implementation, and evaluation. Planning is carried out through coordination among team members and relevant parties, including the preparation of materials, methods, media, and evaluation. Implementation focuses on how activities influence the reduction of stunting rates. Evaluation is conducted through both process and outcome evaluations. The findings regarding the role of the Rumah Pelita team include: leadership and coordination roles, healthcare service roles, health education roles, as well as administrative and monitoring roles. A key success factor is parental participation in fulfilling the nutritional needs of toddlers. Meanwhile, inhibiting factors include participant tardiness and lack of enthusiasm in participating. These findings indicate that the strategies employed contribute to reducing stunting rates and support the zero stunting program in Semarang City.